Implantation of an Actifit(®) Polyurethane Meniscal Scaffold 18 Months After Subtotal Lateral Meniscectomy in a 13-Year-Old Male Adolescent - Accadbled, Franck (Am J Case Rep, 2020)
Patient: Male, 13-year-old Final Diagnosis: Meniscectomy Symptoms: Knee joint pain Medication: — Clinical Procedure: Arthroscopy Specialty: Orthopedics and Traumatology OBJECTIVE: Unusual setting of medical care BACKGROUND: Implantation of the Actifit(®) polyurethane meniscal scaffold is indicated for knee pain after partial meniscectomy in adults who are skeletally mature. This report is of a case of implantation of an Actifit(®) polyurethane meniscal scaffold 18 months after subtotal lateral meniscectomy in a 13-year-old male adolescent. CASE REPORT: A 13-year-old male presented with right knee pain, localized to the lateral joint, 18 months after undergoing subtotal lateral meniscectomy. Magnetic resonance imaging (MRI) of the knee showed a complete amputation of the lateral meniscal middle segment with subchondral bone damage. Arthroscopic exploration of the knee joint showed a subtotal posterior and middle lateral meniscectomy and a 4 cm(2) area of International Cartilage Repair Society (ICRS) grade 3 cartilage damage on the posterior aspect of the lateral tibial plateau. The antero-lateral portal was enlarged to introduce the Actifit(®) scaffold. The implant was secured using three all-inside Fast-Fix(®) sutures and three outside-in vertical sutures, which rapidly reduced the pain symptoms. At five-year follow-up, the patient reported no pain, and he had resumed sporting activities and recovered a full knee range of motion at 0/0/145°. MRI showed a type 2 meniscal implant shape and size, according to the Genovese MRI score. The ICRS MRI score was stable at grade 3b. CONCLUSIONS: This case showed that the use of the Actifit(®) polyurethane meniscal scaffold is an option for the treatment of knee pain after partial or subtotal meniscectomy in skeletally immature patients, resulting in a stable functional outcome at five-year follow-up.